Storytelling-case archetype decoding and assignment manual (SCADAM) - Woodside, Arch G.; Sood, Suresh C. (Emerald, 2016)
Storytelling-case archetype decoding and assignment manual (SCADAM) reviews cultural and tourism/hospitality applications of Carl Jung's work on archetypes in shaping behavior and unconscious/conscious thought. SCADAM includes a testing manual on how to use Donald T. Campbell's "degrees of freedom" (DOF) test for story-archetype assignments of what consumers and brands tell about consumption experiences of product/service brands, places, and drama/life enactments. SCADAM includes assignment testing and example scoring for each of 12 archetypes: 1. Caregiver (CA); 2. Creator (CR); 3. Everyman/woman (EV); 4. Explorer (EX); 5. Hero (HE); 6. Innocent (IN); 7. Jester (JE); 8. Lover (LO); 9. Magician (MA); 10. Ruler (RU); 11. Sage (SA); 12. Shadow (SH). SCADAM increases accuracy of researchers' interpretations of consumers' (emic) interpretations of dramas in consumption experiences; SCADAM provides for comparing DOF testing in scoring alternative archetypes. Thus, this manual provides tools for confirming relevancy and falsifying incorrect archetype assignments of stories consumers and brands tell. SCADAM builds on prior studies in the literature by the authors and colleagues.
Keywords: Jung, C. G. -- (Carl Gustav), -- 1875-1961.; Consumer behavior.; Marketing -- Psychological aspects.; Consumers -- Attitudes.; Archetype (Psychology); elektronické knihy; electronic books